2020
DOI: 10.3389/fcell.2020.598078
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Mfn2 Overexpression Attenuates Cardio-Cerebrovascular Ischemia–Reperfusion Injury Through Mitochondrial Fusion and Activation of the AMPK/Sirt3 Signaling

Abstract: Mitochondria are potential targets for the treatment of cardio-cerebrovascular ischemiareperfusion (I/R) injury. However, the role of the mitofusin 2 (Mfn2) protein in regulating mitochondrial fusion and cell survival has not been investigated. In the present study, an adenovirus-mediated Mfn2 overexpression assay was performed to understand the effects of Mfn2 on mitochondrial function and cell damage during cardiocerebrovascular I/R injury. After exposure to I/R injury in vitro, the transcription and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Specifically, Janus-activated kinase 2(JAK2)/STAT3 pathway plays a functional role in blocking cell apoptosis induced by CI/RI [ 15 ]. Mitofusin-2 (Mfn2) is a mitochondrial fusion factor that could protect against cardio-cerebrovascular I/RI [ 16 ] and ameliorate hypoxia-induced neuronal apoptosis in ischemic brain damage [ 17 ]. It has been also recorded that Mfn2 exerts protective effect on CI/RI [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Janus-activated kinase 2(JAK2)/STAT3 pathway plays a functional role in blocking cell apoptosis induced by CI/RI [ 15 ]. Mitofusin-2 (Mfn2) is a mitochondrial fusion factor that could protect against cardio-cerebrovascular I/RI [ 16 ] and ameliorate hypoxia-induced neuronal apoptosis in ischemic brain damage [ 17 ]. It has been also recorded that Mfn2 exerts protective effect on CI/RI [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mitochondrial fusion may have some compensatory effects on mtDNA mutation ( Chen et al, 2010 ). Liu et al (2020) found that overexpression of Mfn2 can increase MMP, enhance mitochondrial fusion, reduce mitoROS accumulation, activate the AMPK/SIRT3 signaling pathway, and prevent cardio-cerebrovascular ischemia/reperfusion (I/R) damage.…”
Section: Novel Mechanistic Insights: From Mitochondrial Dynamics To Atherosclerosismentioning
confidence: 99%
“…It should be emphasized that mfn1 and mfn2 play a controversial part in the regulation of mitophagy [ 41 ]. Depletion of both mfn1 and mfn2 in murine cardiomyocytes caused the accumulation of defective mitochondria by inhibiting mitophagy [ 42 ]. In contrast, an active role of mfn2 in preventing mitophagy was also proposed, associating with the maintenance of ER-mitochondrial contacts [ 43 ].…”
Section: Discussionmentioning
confidence: 99%